Sectionalization of degraded polymeric cable with multiple joints using TDR technique - Kuan T.M.; Ariffin A.M.; Raymond W.J.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
MATLAB; Polymers; Time domain analysis; Cable replacement; Fault localization; Insulated cables; Multiple joints; Polymeric cables; TDR techniques; Time-domain reflectometry techniques; XLPE cables; Cables